The impact of educational accountability on the performance of teachers in the schools of the Wilayat of Basher in the Sultanate of Oman - Alabri, Abdulsalam Salim; Adnan, Mohamad Azrien Mohamad; Jamil, Asyraf Isyraqi (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to know the impact of educational accountability on the performance of teachers in the schools of the state of Bowsher in the Sultanate of Oman. Computer conducted the questionnaire, and the results of the study showed a positive correlation between the application of accountability and the high performance of teachers. The study recommended the need to develop academic courses in colleges of education related to educational accountability. The researchers also suggested conducting a study on educational governance in light of the Oman 2040 vision, and studying the role of the Omani Authority for Academic Accreditation and Quality Assurance of Education in pushing the educational sector to activate accountability and accountability.
Keywords: educational accountability; teacher performance; Wilayat of Basher